2003
DOI: 10.1088/0953-2048/16/10/303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ca doping on microstructural and superconducting properties of DyBa2Cu3O7  /Caz(0  z  0.2) ceramics

Abstract: Using bright-field and energy selective x-ray analysis techniques in transmission electron microscopy, we have studied the effect of Ca doping on the microstructural and superconducting properties in DyBa 2 Cu 3 O y /Ca z (z = 0, 0.05, 0.1 and 0.2) ceramics, i.e. for the case when Ca was added in excess to the stoichiometric 123 composition. It was found that in this case approximately half of the added Ca amount entered the 123-lattice. Thus, in the composition with nominal z = 0.1 (0.77 at%) average Ca conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…This corroborates the observations in figure 4(c). This way it markedly helps to transform grain boundary junctions from S-I-S to S-N-S type as extensively reported elsewhere [8][9][10]. For a 2% doped sample the observed increase in j c , however, outweighs the increase in volume fraction which suggests the possible addition of new pinning centres which were previously not present in the pristine sample.…”
Section: Flux Pinning and J C (B) In Ca-doped Samplessupporting
confidence: 67%
See 1 more Smart Citation
“…This corroborates the observations in figure 4(c). This way it markedly helps to transform grain boundary junctions from S-I-S to S-N-S type as extensively reported elsewhere [8][9][10]. For a 2% doped sample the observed increase in j c , however, outweighs the increase in volume fraction which suggests the possible addition of new pinning centres which were previously not present in the pristine sample.…”
Section: Flux Pinning and J C (B) In Ca-doped Samplessupporting
confidence: 67%
“…Incidentally, Zn produces the largest T c depression [7] and is found to have a relatively larger effect on j c (B) than Ni [5]. Besides the above dopants, several authors [8][9][10] have reported Ca substitution to dramatically improve intergranular j c of RE-123 by transforming the grain boundary S-I-S junctions to S-N-S type to marginalize the weak link effect. Ca, at grain boundaries, is believed to significantly lower the boundary resistivity.…”
Section: Introductionmentioning
confidence: 99%
“…A complete list of the studied samples is given in table 1. It is seen that Ca doping leads to a substantial decrease in grain size, as was already noted in our previous paper [6]. The normal state resistivity at room temperature was nearly the same in undoped and Ca-doped samples for both T oxg .…”
Section: Superconducting Propertiessupporting
confidence: 84%
“…The obtained difference between the nominal and real concentration of Ca in 123 grains can be associated with the presence Ca in secondary phases. As already shown in [6], Ca promotes the formation of some new (Dy)(Ba)(Cu)O phase in the proportion 1:(1.2-1.5):(2-4):(4-8) with 0.5-2.0 at.% Ca and in the proportion 1.2:1:(2-2.5):(3.5-4) with 0.15-0.5 at.% Ca. Calcium also entered in a very limited amount ( 0.15 at.%) into the 'green' phase.…”
Section: Superconducting Propertiessupporting
confidence: 72%
See 1 more Smart Citation